SAR Satellite Imagery Reveals the Impact of the Covid-19 Crisis on Ship Frequentation in the French Mediterranean Waters - Pita, Ignacio; Seguin, Raphael; Shin, Yunne-Jai; Viguier, Pauline; Catry, Thibault; Devillers, Rodolphe; Mouillot, David (Frontiers in Marine Science, 2022)
The Covid-19 pandemic is the latest example in a growing number of health, social, economic, and environmental crises humanity is facing. The multiple consequences of this pandemic crisis required strong responses from governments, including strict lockdowns. Yet, the impact of lockdowns on coastal ecosystems and maritime activities is still challenging to quantify over large spatial scales in comparison to the pre-Covid period. In this study, we used an object detection algorithm on Synthetic Aperture Radar (SAR) images acquired by the two Sentinel-1 satellites to assess the impact of the Covid-19 crisis on the presence of boats before, during and after lockdown periods in the French Mediterranean Exclusive Economic Zone. During the French most severe lockdown period (March – May 2020), we observed that ship frequentation remained at the same level from March to July 2020, instead of rising towards the summer peak like in previous years. Then, ship frequentation increased rapidly to a normal level in August 2020 when restrictions were lifted. By comparing morning and evening (7:00 am and 7:00 pm) ship frequentation during this period to pre-Covid years, we observed contrasting patterns. On the one hand, morning detections were particularly high, while on the other hand evening detections were significantly lower and less concentrated in coastal touristic waters than in previous years. Overall, we found a 9% decrease in ship frequentation between the year 2020 and the 2017-2019 period, with a maximum of 43% drop in June 2020 due to the lockdown. So, the Covid -19 crisis induced only a very short-term reduction in maritime activities but did not markedly reduce the annual ship frequentation in the French Mediterranean waters. The satellite imagery approach is an alternative method that improves our understanding of the pandemic impacts at an unprecedented spatiotemporal scale and resolution.